PENGARUH MEKANISME KOMITE AUDIT TERHADAP MANAJEMEN LABA: STUDI EMPIRIS PADA PERUSAHAAN YANG MELAKUKAN MANAJEMEN LABA UNTUK MENGHINDARI KERUGIAN - Vajriyanti, Eva; Subekti, Imam; Ghofar, Abdul (Universitas Muhammadiyah Malang)
This study is conducted on companies in Indonesia during 2012-2015. This research is conductedto test whether manager performs earnings management to avoid negative earnings. This studyalso examines the effect of the mechanism of audit committee on earnings management. Thisstudy provides empirical evidence that manager performs earnings management to avoid negative earnings by increasing production costs and minimizing cash flow from operations. Thisstudy also provides empirical evidence that the mechanism of audit committee which consist ofthe size of audit committee, expertise of audit committee, as well as the audit committee meeting has no effect on earnings management by increasing production costs and minimizing cashflow from operations.Key words: Accrual earnings management, Mechanism of audit committee, Real earningsmanagement.